A new species of Phytoscutus Muma (Acari: Mesostigmata: Phytoseiidae) from Amazonas state, Brazil, with redefinition of the sexpilis species group Chant & McMurtry and a key to the world species of the genus - Demite, Peterson R.; Cruz, Wilton P. da [UNESP]; Cavalcante, Ana Cristina C. (Systematic & Applied Acarology Soc London, Natural History Museum, 2019)
A new species, Phytoscutus moraesi n. sp., is described based on specimens collected on Arecaceae plants, in Amazonas state, Brazil. Phytoscutus moraesi n. sp. is included in the sexpilis species group Chant & McMurtry, which is herein redefined to accommodate this new species. A key is provided for the world species of Phytoscutus.
Keywords: Amazon Biome; Amblyseiinae; Arecaceae; biological control; predator